Summer of hate : Charlottesville, USA - Spencer, Hawes (University of Virginia Press, 2018)
In August 2017, violence erupted in Charlottesville, Virginia, during two days of demonstrations by white supremacists, neo-Nazis, and counterprotesters, including members of antifa and Black Lives Matter. Ostensibly motivated by the city's plans to remove Confederate statues from two public parks, members of the alt-right descended first on the University of Virginia and then, disastrously, on the city's downtown. As these violent and ultimately deadly events gripped the attention of the nation, extensive coverage in both mainstream and fringe media promulgated competing narratives. Summer of Hate is the investigative journalist Hawes Spencer's unbiased, probing account of August 11 and 12. Telling the story from the perspectives of figures on all sides of the demonstrations, Spencer, who reported from Charlottesville for the New York Times, carefully recreates what happened and why. Focusing on individuals including activists, city councilors, faith leaders, and the police, Spencer creates an objective, panoramic narrative that renders these dramatic events, and the ongoing conflicts underlying them, in all their complexity.